2019
DOI: 10.1088/1755-1315/403/1/012230
|View full text |Cite
|
Sign up to set email alerts
|

Simulation modeling of changes in demand for rail transportation

Abstract: The purpose of the paper is to justify the use of the intersectoral balance model for forecasting the demand for rail transportation in the face of significant changes in commodity markets. The theoretical basis of the study is the algebraic theory of the analysis of the input-output model. The methodology is based on the balance method. The modeling procedure comes down to solving a system of linear equations in which the coefficients are cost coefficients for production. The modeling information base include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…When developing a model of reliability of the railway freight forecasting system, we find confirmation of the reliability of the data architecture proposed by us, which ensures the effectiveness of managerial decision-making in conditions of uncertainty and the achievement of complex goals within the framework of developed transport development strategies [10]. The parameters of modeling the demand for rail transportation, taking into account structural changes affecting the activities of the main sectors of the national economy [11], can significantly improve the analytical base for the development of freight forecasts. In general, a significant amount of research indicates the importance of finding optimal solutions when predicting the volume and structure of cargo transportation in the current instability of the transport services market and numerous logistical sanctions restrictions [12,13].…”
Section: Discussionmentioning
confidence: 58%
“…When developing a model of reliability of the railway freight forecasting system, we find confirmation of the reliability of the data architecture proposed by us, which ensures the effectiveness of managerial decision-making in conditions of uncertainty and the achievement of complex goals within the framework of developed transport development strategies [10]. The parameters of modeling the demand for rail transportation, taking into account structural changes affecting the activities of the main sectors of the national economy [11], can significantly improve the analytical base for the development of freight forecasts. In general, a significant amount of research indicates the importance of finding optimal solutions when predicting the volume and structure of cargo transportation in the current instability of the transport services market and numerous logistical sanctions restrictions [12,13].…”
Section: Discussionmentioning
confidence: 58%
“…Based on the results of the literature analysis [2][3][4][5], it can be concluded that the main type of problems hindering the development of the high-speed freight transportation market consists in technical and technological barriers, and the lack of full and timely financing of development projects in progress.…”
Section: The Results Of the Analysismentioning
confidence: 99%
“…The nature and scale of the problems studied, connects the study with the works of Russian scientists and practitioners [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%